PENGARUH MULSA PLASTIK HITAM PERAK DAN JARAK TANAM PADA HASIL BAWANG MERAH (Allium cepa fa. ascalonicum, L.) VARIETAS BIRU LANCOR - Sukron Mahmudi; Hadi Rianto; Historiawati Historiawati (JURNAL VIGOR, 2017)
The research is to study the effect of the use of black-silveric plastic mulch and planting distance on yield of onion (Alliumcepa fa. ascalonicum, L.) Lancor Blue variety. The research had been conducted in October 23 until December 12, 2014 in Digelan, Soropadan Village, District Pringsurat, Regency Temanggung. Altitude of 480 m, the type of soilis Alluvial and pH 6,5. Methods of research is a factorial experiment (2x3) arranged in a randomized complete block design, replicated three times. The first factor is mulching: without mulch and black-silveric plastic. The second factoris planting distace of 10 cm x 15 cm, 10 cm x 20 cm and 10 cm x 25 cm. The reult showed that the use of black-silveric plastic mulch enhances all observed parameters except relative water content. Planting distace of 10 cm x 25 cm resulted in the highest number of bulbs per hill and highest weight of dried bulbs. Mulching on different planting distance has regular respon on observed parameters.